2020
DOI: 10.1007/s00339-020-3414-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and structure of Pb thin films grown on Si(111) by pulsed laser deposition

Abstract: Pulsed laser deposition (PLD) is a versatile thin film deposition technique in which high powered laser beam interacts with a target material inside an ultrahigh vacuum chamber. Highly energetic particles such as electrons, atoms, protons, and ions generate a plasma plume that directed towards a substrate material where recondenses form a thin film. PLD is an effective and reliable method to create varieties of thin films such as metal, polymer, and ceramic for many technologically essential applications. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…With temperature increase, the film became textured, and for a substrate temperature of 650−850 • C, a mix of cubic NbN and hexagonal phases was formed, and the surface roughness of the NbNx films increased as the temperature was raised from 450 • C to 850 • C. For Pb films, it was shown that when the substrate temperature was raised from RT to 300 • C, the film growth mechanism changed from Volmer-Weber to cluster formation mode. When the temperature was raised to values close to the melting temperature of Pb, the Ostwald ripening effect was observed [67]. In our case, the melting temperature of HA was far from the substrate temperature range; however, the results suggest that the variations in substrate temperature affected the nucleation-growth process, allowing smaller particles to conglomerate and possibly form larger crystals.…”
Section: Resultsmentioning
confidence: 48%
“…With temperature increase, the film became textured, and for a substrate temperature of 650−850 • C, a mix of cubic NbN and hexagonal phases was formed, and the surface roughness of the NbNx films increased as the temperature was raised from 450 • C to 850 • C. For Pb films, it was shown that when the substrate temperature was raised from RT to 300 • C, the film growth mechanism changed from Volmer-Weber to cluster formation mode. When the temperature was raised to values close to the melting temperature of Pb, the Ostwald ripening effect was observed [67]. In our case, the melting temperature of HA was far from the substrate temperature range; however, the results suggest that the variations in substrate temperature affected the nucleation-growth process, allowing smaller particles to conglomerate and possibly form larger crystals.…”
Section: Resultsmentioning
confidence: 48%
“…Among the different deposition methods, the pulsed laser deposition (PLD) technique is considered a highly versatile technique for a growing number of thin film applications [5][6][7][8][9][10][11][12]. PLD uses high-energy laser pulses to vaporize the surface of a solid target inside a vacuum chamber and condenses the vapor on a substrate to form a film.…”
Section: Introductionmentioning
confidence: 99%